Pediatric skin disorders in a Portuguese hospital. - Leite, I.; Moreira, A.; Guedes, R; Baptista, A.; Osório Ferreira, E. (European Journal of Pediatric Dermatology, 2010)
We performed a survey of the new referrals to the Pediatric Dermatology consultation in a Portuguese hospital over ten years. A total of 3325 patients were studied. Infectious diseases were the most common, with 738 children (22.2%) followed by nevi with 678 (20.4%), eczemas with 535 (16.1%), adnexal diseases with 353 (10.6%) and pigmentary disorders with 183 (5.5%). Epidemiologic studies are important since they may improve preventive medicine in order to decrease cutaneous diseases in children.